Dynamic Changes in Hepatitis A Immunity in Regions with Different Vaccination Strategies and Different Vaccination Coverage - Karen K. Kyuregyan; Maria A. Lopatukhina; Fedor A. Asadi Mobarkhan; Vera S. Kichatova; Ilya A. Potemkin; Olga V. Isaeva; Anastasia A. Karlsen; Elena Yu. Malinnikova; Alla N. Kaira; Tatyana V. Kozhanova; Victor A. Manuylov; Elena P. Mazunina; et al. (Vaccines, 2022)
The data on hepatitis A virus (HAV) seroprevalence are critical for the implementation of a universal mass vaccination (UMV) strategy. The latter has not been implemented in Russia; however, regional child vaccination programs have been adopted in some parts of the country. The aim of this study is to assess changes in HAV immunity within the last decade in regions of Russia with different vaccination strategies and different vaccination coverage rates. In regions where UMV has not been implemented and HAV vaccination coverage rates do not exceed the national average, the 50% seroprevalence threshold has shifted in the Moscow region from people aged under 40 years in 2008 to people aged over 59 years in 2020, and from people aged under 30 years to people aged over 40 years in the Khabarovsk region. In two regions (Yakutia and Sverdlovsk), a two-dose-based UMV scheme has been in place since 2011 and 2003, respectively, and in Tuva single-dose child immunization was launched in 2012. These regional programs have resulted in a significant increase in HAV seroprevalence in children and adolescents. In Yakutia, 50% herd immunity had been achieved by 2020 in age groups under 20 years, compared to 20–30% seroprevalence rates in 2008. In the Sverdlovsk region, HAV immunity has increased to >65% over the decade in children aged over 10 years, adolescents and young adults, whereas it declined in older age groups. However, a three-fold drop in HAV immunity has occurred in children under 10 years of age, reflecting a significant decline in vaccination coverage. In Tuva, HAV immunity rates in children under 10 years old increased two-fold to exceed 50% by 2020. These data suggest that UMV should be implemented on a national level. Measures to control vaccination coverage and catch-up vaccination campaigns are recommended in order to maintain the effectiveness of existing HAV vaccination programs.